MODIFIED SHELL & TUBE TYPE HEAT EXCHANGER (International Journal of Engineering Sciences & Management Research, 2017)
Heat exchanger is a device which provides a flow of thermal energy two or more fluids at a different temperature. There are many problems created in the segmental heat exchanger during its working. The main reason of that is construction of shell & tubes, type of fluid used, type of material etc., The purpose of this work is to design the shell and tube heat exchanger is one of the majority type of liquid –to –liquid heat exchanger. Since the important design parameters such as the tube length, and tube layer as well as baffle spacing has a direct result on decrease in pressure and temperature.. The newly designed heat exchanger obtained a maximum heat transfer coefficient and less pressure decreases, the result shows that the performance is increases